Mammary angiosarcoma in an adolescent : a case report - Teh, SX; Norlia Abdullah,; Nordashima AS,; Elia Shazniza S,; Marfuah NE,; Shahizon Azura MM, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mammary angiosarcoma is an extremely rare and highly aggressive malignant tumour of vascular origin. It can be divided into 2 types; primary angiosarcoma which develops de-novo and secondary angiosarcoma which occurs as a complication of post-radiotherapy or chronic lymphoedema. We present a case of a 19-year-old adolescent with a large right breast mass for the duration of 9 months. The core biopsy was reported as an angiosarcoma. She did not have any previous breast pathology. She underwent a right mastectomy, followed by adjuvant radiotherapy. She developed scalp and skull metastases 5 months postsurgery and was currently undergoing palliative chemotherapy. There is a lack of international consensus on the management of mammary angiosarcoma due to its rarity. The main modality of management is surgery, preferably mastectomy. Radiotherapy and chemotherapy are sometimes given in an attempt to prevent or treat local recurrence and metastasis.